1999
DOI: 10.1034/j.1399-3046.1999.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Epstein–Barr virus status and post‐transplant lymphoproliferative disease in pediatric thoracic transplantation

Abstract: Epstein-Barr virus (EBV)-associated post-transplant lymphoproliferative disease (PTLD) is a serious complication of organ and bone marrow transplantation. The importance of EBV matching between recipient and donor remains unclear. Between October 1987 and December 1997, 64 pediatric cardio-pulmonary transplants were performed at this center (58 hearts, two heart/lungs, four sequential single lungs). The EBV viral capsid antigen (VCA) immunoglobulin G (IgG) status of both donor and recipient was determined at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…This phenomenon has also been noted by others (10,17,18), although isolated GI disease with a good prognosis has been reported (1,7). Others have reported intrathoracic PTLD to be a fairly common complication following heart transplantation (1-3, 7, 10, 14, 18, 24, 29, 34); we had no cases of intrathoracic disease as a first presentation of PTLD, as has been the case in other series as well (11,24,25,30).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This phenomenon has also been noted by others (10,17,18), although isolated GI disease with a good prognosis has been reported (1,7). Others have reported intrathoracic PTLD to be a fairly common complication following heart transplantation (1-3, 7, 10, 14, 18, 24, 29, 34); we had no cases of intrathoracic disease as a first presentation of PTLD, as has been the case in other series as well (11,24,25,30).…”
Section: Discussionsupporting
confidence: 88%
“…There was no significant association between PTLD development and sex, race, donor age, recipient diagnosis, the number of rejection episodes (treated or untreated) occurring between the time of transplant and the time of development of PTLD, or the number of times that lympholytics were used prior to development of PTLD. Most [but not all (25)] studies show that patients undergoing primary or reactivated EBV infection following transplantation are at the highest risk for developing PTLD, perhaps because they harbor more virus (26). The higher incidence of primary EBV infection in children accounts for the higher incidence of PTLD in pediatric as compared with adult transplant recipients (3, 6–8, 17, 18).…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition of donor EBV is a risk factor for PTLD development in a previously seronegative transplant recipient [19]. In a large series of renal transplant recipients, 86% of paediatric patients who were EBV negative received a kidney from an EBV-positive donor, compared with only 50% of EBV-negative adults who received a seropositive graft [20]. Also, it has been shown that in the transplant recipient primary EBV disease develops later, is more likely to be clinically symptomatic, and is associated with a greater rise in serum creatinine and risk of graft loss than reactivation disease [16].…”
Section: Seronegative Recipient Statusmentioning
confidence: 99%
“…Seronegative patients who receive organs from a seropositive donor are at particular risk for infection from the graft at a time when immunosuppression is maximal (2). Recipients of L‐HLTx are among the highest risk groups (3). Prompt diagnosis is essential in preventing the serious complications associated with this disorder (4).…”
mentioning
confidence: 99%